The demand for savings services among the urban poor - evidence from the Khayelitsha panel study (2000-2004) - Esson, Ross (School of Economics, 2024)
In signing its charter in 2002, the South African financial sector voluntarily committed itself to providing first order retail financial service access to the un-banked by 2008. Although much of the media attention and academic literature has been focused towards the challenge of providing basic transaction services, the charter has also set out specific savings targets for the 2008 deadline. It specified that by 2008, 80% of the poorest half of the South African population (as judged by living standard measures (LSMs)) should have effective access to appropriate savings products and services (National Treasury. 2002:9). Access to retail transaction banking services is the first key step to accessing more sophisticated financial products and services such as bank savings accounts, pension funds and unit trusts (Porteous, 2004: 21). By focusing on savings, this paper explores this element of the "financial services deepening" debate. If the savings services' net is to be extended through the design of more appropriate savings products for the poor, it is necessary to identify the factors that drive people to save in areas of high unemployment and poverty.